Paw patrol pawsome search - Moore, Harry; Petrossi, Fabrizio (Chicago, USA Pi kids, 2020)
Join Marshall, Skye, and all your PAW Patrol pals as you search for hidden things in 7 scenes! Then flip to the end of the book for even more Look and Find challenges. Concepts include counting, rhyming, shapes, and more! Toddlers can search, point, match, and compare all on their own no reading required! Look and Find play encourages focus and exploration, and helps build early learning skills
Hobbies
Keywords: Hobbies